Business Intelligence Viewboard iLearning Media (iMe) Dalam Pengembangan Motivasi Belajar Menggunakan Metode Simple Additive Weighting Pada SMK Pustek Serpong - Sari, Herva Emilda; Adam, Helmi (Technomedia Journal, 2019)
Media visualization of the digital era, is a significant development in the industrial and educational world. Where in packaging the results of the report are required to be a visualization that can be received quickly, briefly, and can be received efficiently to the recipient of information. In the application sector, processing data into information can be displayed with a graph model. This graphical model is able to help recipients of information to be able to capture various information quickly, efficiently, and provide information needed to determine future decision development. The use of business intelligence in implementing the viewboard on learning, supports the creation of complicated information delivery, so that it can be consumed and accepted easily. In the communication, the viewboard model becomes a link between data from Rinfo spreadsheets, to be displayed as a form of graphical information that can facilitate recipients of information in increasing the motivation to make decisions from the graphical information displayed. In processing data into Rinfo spreadsheet information, the calculation uses the Simple Additive Weighting (SAW) method, in the process there is cluster division and weighting of values. The results will be used as decision support information on the graphical viewboard that is displayed attractively, will produce a decision making system of information that is faster, easier and more efficient. Keywords: Viewboard, information, graphics, business intelligence